(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Textiles that use electrospun nanofibre membranes (ENMs) in laminated configurations recently achieved substantial progress in three application areas, including robotic skins, electronic sensors, and medical textiles. Research evaluates nanofibre-laminated textile bonding strength by using multiple experimental methods. The study presents the development of three different textile composites in which polyacrylonitrile (PAN) polymer was treated with electrospinning on fabric through various adhesive techniques. The testing evaluates the different nanofibre-fabric bonding methods using T-peel tests to determine their effectiveness. The direct electrospinning methods used to produce laminated textiles led to negligible or no attachment between fabric materials and ENMs. The electrospinning process led to initial ENM layer adhesion when an adhesion agent was incorporated during the process. The tested composite achieved a 60% higher strength after using adhesive pressure to create it. Research findings show that applying an adhesive agent with pressure between textile materials and ENMs produces optimal interfacial adhesion during the fabrication of laminated textile composites.